An adaptive energy efficient protocol in media access control - Abduljaleel, Uday; Akbari, Ayyoub; Khatun, Sabira (2009)
In this paper, we propose a novel pe-frame based TPC protocol, an Adaptive Energy efficient protocol in Media Access Control (AE-MAC), in ad-hoc networks using IEEE 802.11 at low PHY rate. To avoid interference, improve throughput, and save energy, AE-MAC adaptive looks for the optimal transmit power based on the network interference and data payload. Transmit Power Control (TPC) protocols is proposed to address the limited power supplies in ad-hoc networks. However,most of the previous work minimize the transmit power without considering both the energy wasted in collisions and energy used to overcome the interference from all the interfering nodes existing in the network. Previous experiments show that optimal transmit power for the maximum throughput and per frame minimum consumed energy exists and occurs when the power level is sufficient to avoid interference, and causes the least contention between nodes. AE-MAC is validate via simulations and is shown to outperform several existing TCP protocols.